The Responses of the Ovary and Eyestalk in Exopalaemon carinicauda under Low Salinity Stress - Xiuhong Zhang; Jiajia Wang; Chengwei Wang; Wenyang Li; Qianqian Ge; Zhen Qin; Jian Li; Jitao Li (Fishes, 2022)
As a euryhaline shrimp, the ridgetail white prawn Exopalaemon carinicauda is strongly adaptable to salinity. Exploring the effect of long-term low salinity stress on ovarian development in E. carinicauda is essential to promote its culture in a non-marine environment. In this study, we performed biochemical assays and ovary histology analysis, finding that the E. carinicauda can adapt to low salinity stress through osmotic adjustment, and there was no substantial damage to the ovary of E. carinicauda under low salinity stress. Then, the ovarian development of E. carinicauda under low salt stress was further explored by RNA sequencing of eyestalk and ovarian tissues. A total of 389 differentially expressed genes (DEGs) in ovary tissue were identified under low salinity stress, and the 16 important DEGs were associated with ovarian development. The majority of the DEGs were enriched in ECM-receptor interaction, folate biosynthesis, arginine biosynthesis, insect hormone biosynthesis and lysosome which were involved in the ovarian development of E. carinicauda. A total of 1223 DEGs were identified in eyestalk tissue under low salinity stress, and the 18 important DEGs were associated with ovarian development. KEGG enrichment analysis found that ECM-receptor interaction, folate biosynthesis, lysosome, arginine biosynthesis and retinol metabolism may be involved in the ovarian development under low salinity stress. Our results provided new insights and revealed new genes and pathways involved in ovarian development of E. carinicauda under long-term low salinity stress.